2002
DOI: 10.1097/00005110-200204000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Emotional Intelligence

Abstract: Emotional intelligence is being touted in the popular literature as an important characteristic for successful leaders. However, caution needs to be exercised regarding the connection between emotional intelligence and workplace success. The author contrasts 2 current models of emotional intelligence, the measurements being used, and the ability of emotional intelligence to predict success. Implications for the workplace are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…These studies extended knowledge of emotional labor among occupations such as police officers (Ehrlich, 1999;Stenross & Kleinman, 1989); firefighters (Scott & Myers, 2005); corrections officers (Tracy, 2005); emergency responders (Tracy & Tracy, 1998); nurses (Bolton, 2001;Vitello-Cicciu, 2003); midwives (Hunter, 2001); mortuary scientists (Cahill, 1999); social workers (Barlow & Hall, 2007;Leeson, 2010); teachers (Hebson, Earnshaw, & Marchington, 2007;Oplatka, 2007); and hospitality providers (Payne, 2009). While training in these fields often included consideration of emotional labor topics and skills, researchers found that workers in these fields also reported acquiring emotion management skills through more informal, social means such as discussing cases with peers, consulting with a mentor, or reflecting upon recent performances.…”
Section: Jacqueline M Zalewski and Leigh S Shaffermentioning
confidence: 93%
See 1 more Smart Citation
“…These studies extended knowledge of emotional labor among occupations such as police officers (Ehrlich, 1999;Stenross & Kleinman, 1989); firefighters (Scott & Myers, 2005); corrections officers (Tracy, 2005); emergency responders (Tracy & Tracy, 1998); nurses (Bolton, 2001;Vitello-Cicciu, 2003); midwives (Hunter, 2001); mortuary scientists (Cahill, 1999); social workers (Barlow & Hall, 2007;Leeson, 2010); teachers (Hebson, Earnshaw, & Marchington, 2007;Oplatka, 2007); and hospitality providers (Payne, 2009). While training in these fields often included consideration of emotional labor topics and skills, researchers found that workers in these fields also reported acquiring emotion management skills through more informal, social means such as discussing cases with peers, consulting with a mentor, or reflecting upon recent performances.…”
Section: Jacqueline M Zalewski and Leigh S Shaffermentioning
confidence: 93%
“…Course work in professional curricula often includes modules devoted to emotion labor. For example, nursing students learn the importance of emotional labor when they are taught techniques for coping with the emotional demands of nursing roles as well as skills in facilitating the emotional tone in their conversations with hospital staff (Davies, 2009;Vitello-Cicciu, 2003). Many general education courses also provide a very useful context for gaining knowledge of the dynamics of human emotions and deliberately practicing emotional labor.…”
Section: Advising the Development Of Emotional Labor For Career Prepamentioning
confidence: 99%
“…Vitello-Cicciu found that chief nursing officers (CNOs) who had higher EI scores on the MSCEIT has less turnover at the director level than did those CNOs who scored lower on the MSCEIT. [3233] Typically, the number of directors who report to the CNO is less than the number of direct reports to a front-line Nurse Manager.…”
Section: Limitationsmentioning
confidence: 99%
“…According to Vitello-Cicciu (2002), the ability to identify emotions in oneself can be enhanced by self-reflection. Reflection in nursing practice, education and research has spread globally and the emphasis placed on development of self-awareness as a leadership strategy has contributed to this increase (Horton-Deutsch & Sherwood 2008).…”
Section: Recommendationsmentioning
confidence: 99%